Influence of potassium fertilizers on stable carbon isotopic ratio in rice - S. M. A, Nuraini; M. A., Adibah; Sulaiman, M. F. (Malaysian Society of Soil Science, 2022)
Isotope measurements are associated with critical plant resources. Thus, stable rice crop's carbon isotope composition in response to potassium (K) fertilizer was determined,since K is a primary plant nutrient that plays a major role in achieving maximum economic yields. Rice plants were grown in the field and rain shelter under five treatments, which are T1 (no-K), T2 (MOP), T3 (SOP), T4 (Polyhalite) and T5 (conventional fertilizer). The fertilizers were applied 3 days after planting (DAP), 15 DAP, 55 DAP and 75 DAP. Leaf photosynthesis and stomata conductance measurements were taken 85 DAP. The samples were then dried and reserved for carbon isotope analyses. Photosynthesis declined due to K deficiency in the no-K treatment. From this research, we can conclude that stomatal conductance is affected by K fertilizer application where it controls the carboxylation efficiency which may affect the rate of photosynthesis. Later, photosynthesis may influence the discrimination of δ13 isotope value. There is discrimination against this heavier isotope of CO2, this is because CO2 diffuses through stomata by carbon 12 faster than carbon 13 so that is why there is discrimination against carbon 13 in the stomata.